Personality Traits and Escape Behavior in Traffic Accidents: Experiment and Modeling Analysis - Xie, Yaohua; Xu, Xueming; An, Wenjuan (Frontiers in Psychology, 2022)
In this paper, we try to reveal the relationship between personality traits and escape behavior in traffic accidents. Different from common computer simulations, this study, for the first time, established a real database recording subjects’ escape behavior and personality traits when watching a first person driving video with explosion. Then, we use a modeling method of general linear to establish a quantitative model of the influence of personality traits, explosion and their interaction on escape behavior. In the model, we introduced escape response time, escape time, escape direction, escape speed, escape trajectory and other motion characteristics to study individual escape behavior in accidents. Through the analysis, we concluded several conclusions, including that high neurotic individuals tend to escape with shorter response time and slower speed by choosing doors far from the explosion source. These conclusions may provide some references for the effective escape of the crowd and the successful escape of the individual under traffic accidents.